ANALISIS KELAYAKAN EKONOMI USAHA PENGOLAHAN GULA MERAH DESA LABUAN BAJO KECAMATAN WAKORUMBA UTARA KABUPATEN BUTON UTARA - Rollyani Rollyani; Dasmin Sidu; Rosmawaty Rosmawaty (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This study aims to (1) determine the brown sugar processing process in Labuan Bajo Village, (2) determine the income earned by brown sugar processors in Labuan Bajo Village, and (3) the economic feasibility of brown sugar processing business in Labuan Bajo Village.  carried out in Labuan Bajo Village, North Wakorumba District, North Buton Regency in April-July 2022 with a total of 17 samples selected by census. Data analysis in this study used mixed methods which combines quantitative research methods with qualitative research methods sequentially.  to determine the development of brown sugar processing related to the object of research descriptively, while quantitative methods are used to find out how much income is obtained by brown sugar processors and determine the economic feasibility of whether the business being run is feasible or not. The results show that (1) The process  of  processing brown sugar starting from the tapping process, cooking process, printing process, to the packaging process is still done traditionally. (2) The income obtained by brown sugar processors is Rp. 18 544 307,- months, with an average value of Rp. 1,090 842,-month. (3) Economic feasibility of the brown sugar processing business n gets an RC ratio of Rp 6,2 so that it is declared a profitable and feasible business to run because the R/C value is more than 1(one).